2016
DOI: 10.1016/j.biopsych.2015.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking Reveals Abnormal Visual Preference for Geometric Images as an Early Biomarker of an Autism Spectrum Disorder Subtype Associated With Increased Symptom Severity

Abstract: Background Clinically and biologically, ASD is heterogeneous. Unusual patterns of visual preference as indexed by eye-tracking are hallmarks, yet whether they can be used to define an early biomarker of ASD as a whole, or leveraged to define a subtype is unclear. To begin to examine this issue, large cohorts are required. Methods A sample of 334 toddlers from 6 distinct groups (115 ASD, 20 ASD-Features, 57 DD, 53 Other, 64 TD, and 25 Typ SIB) participated. Toddlers watched a movie containing both geometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
319
5
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(394 citation statements)
references
References 62 publications
41
319
5
12
Order By: Relevance
“…Corbett et al (2014) reported two ASD social-cortisol level groups: the ASD low social motivation group engaged in less social play and expressed higher levels of cortisol in interaction, and the ASD moderate social motivation group engaged in relatively more social play and expressed lower levels of cortisol in interaction. Pierce et al (2015) reported finding two ASD social attention subgroups: 80 % of toddlers with ASD preferred to look at dynamic social images, but 20 % of toddlers with ASD strongly preferred to look at dynamic geometric images. Pierce et al (2015) noted that none of the children in comparison groups, including Btoddlers with typical development, language delay, and global developmental delay as well as unaffected siblings of toddlers with ASD^(p. 6), preferred to look at dynamic geometric images.…”
Section: Distinct Subgroups Have Been Identified Within Asd Social Immentioning
confidence: 99%
See 1 more Smart Citation
“…Corbett et al (2014) reported two ASD social-cortisol level groups: the ASD low social motivation group engaged in less social play and expressed higher levels of cortisol in interaction, and the ASD moderate social motivation group engaged in relatively more social play and expressed lower levels of cortisol in interaction. Pierce et al (2015) reported finding two ASD social attention subgroups: 80 % of toddlers with ASD preferred to look at dynamic social images, but 20 % of toddlers with ASD strongly preferred to look at dynamic geometric images. Pierce et al (2015) noted that none of the children in comparison groups, including Btoddlers with typical development, language delay, and global developmental delay as well as unaffected siblings of toddlers with ASD^(p. 6), preferred to look at dynamic geometric images.…”
Section: Distinct Subgroups Have Been Identified Within Asd Social Immentioning
confidence: 99%
“…Pierce et al (2015) reported finding two ASD social attention subgroups: 80 % of toddlers with ASD preferred to look at dynamic social images, but 20 % of toddlers with ASD strongly preferred to look at dynamic geometric images. Pierce et al (2015) noted that none of the children in comparison groups, including Btoddlers with typical development, language delay, and global developmental delay as well as unaffected siblings of toddlers with ASD^(p. 6), preferred to look at dynamic geometric images. Bishop et al (2016) reported finding two clusters of ASD social impairments.…”
Section: Distinct Subgroups Have Been Identified Within Asd Social Immentioning
confidence: 99%
“…For instance, speed of visuospatial orienting at 3.5 or 7 months of age will predict cognitive and academic performance at the age of 4 and 11 years [38,39]. Similarly, tests assessing infants' attentional bias for faces at 7 months predict socioemotional development at the age of 14 months [40], and reduced face preference is associated with later autism spectrum disorders [41][42][43][44][45][46] and atypical development [47]. Compared with traditional observational methods, eye-tracking-based testing of infants allows for completed automatization of the test procedure, as well as accurate, transparent physiological metrics of the sensory and cognitive processes in infants [33,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Pierce et al (2011), Shi et al (2015) e Pierce et al (2015) utilizam critérios e estímulos similares, baseados no paradigma de movimento biológico, em que definem a duração total da fixação do olhar em movimentos não biológicos como critério de diagnóstico, porém Pierce et al (2011) avaliam crianças de um a três anos, enquanto Shi et al (2015) avaliam crianças de quatro a seis anos.…”
Section: Sistema Diagnóstico De Observação Do Autismo Conhecido Comounclassified
“…Com essa abordagem, Pierce et al (2015) conseguiram distinguir os grupos com uma sensibilidade de 21% e especificidade de 98% para um grupo de 334 crianças, enquanto Shi et al (2015), utilizando uma curva característica de operação do receptor (ROC -do inglês Receiver…”
Section: Sistema Diagnóstico De Observação Do Autismo Conhecido Comounclassified